2022
DOI: 10.14639/0392-100x-n1832
|View full text |Cite
|
Sign up to set email alerts
|

Update of endoscopic classification system of adenoid hypertrophy based on clinical experience on 7621 children

Abstract: SUMMARY Introduction Nasal endoscopy is likely to be the method of choice to evaluate nasal obstruction and adenoid hypertrophy (AH) in children given its excellent diagnostic accuracy and low risk for the patient. The aim of this study was to update the previous classification of AH to guide physicians in choosing the best therapeutic option. Materials and methods This is a retrospective observational study including 7621 children (3565 females; mean age 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Medical management of severe obstructive sleep apnoea during the COVID-19 pandemic, including continuous positive airway pressure therapy in severe cases, showed that this kind of treatment is poorly tolerated, and that surgery remains the gold standard 12 . Normally, stratification of patients according to the endoscopic classification of adenoid hypertrophy is the method of choice to indicate medical or surgical therapy 13 . However, considering that otolaryngologists are at high risk of contagion because of the proximity to superior airways during physical examination and of the aerosolisation of many common procedures including nasopharyngeal fibre-endoscopy 14 , according to our responders, the number of outpatient procedures requiring fibreoptic evaluation significantly decreased during the COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%
“…Medical management of severe obstructive sleep apnoea during the COVID-19 pandemic, including continuous positive airway pressure therapy in severe cases, showed that this kind of treatment is poorly tolerated, and that surgery remains the gold standard 12 . Normally, stratification of patients according to the endoscopic classification of adenoid hypertrophy is the method of choice to indicate medical or surgical therapy 13 . However, considering that otolaryngologists are at high risk of contagion because of the proximity to superior airways during physical examination and of the aerosolisation of many common procedures including nasopharyngeal fibre-endoscopy 14 , according to our responders, the number of outpatient procedures requiring fibreoptic evaluation significantly decreased during the COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, adenoidectomy should be indicated based on persistent respiratory symptoms refractory to clinical treatment, corroborated by the nasofibroscopic finding of adenoid hypertrophy. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that Cassano et al's study included patients with other conditions that can impact sleep quality, such as tonsil hypertrophy and nasal secretions. 18 …”
Section: Discussionmentioning
confidence: 99%
“…If adenoid tissue occupies about 75% of the nasopharynx with partial involvement of the tube ostium and considerable obstruction of choanal openings was classified as grade 3. If adenoid tissue reaches the lower choanal border without allowing visualization of the tube ostium (> 75%) was classified as grade 4 [ 7 ].…”
Section: Methodsmentioning
confidence: 99%